Devotional Poetry, Exceptional Calligraphy, Charming Manuscript: Expression of Religious Emotion in Ḥassan Kāshī’s Haft-Band - Amir H. Zekrgoo, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
The Middle Eastern manuscript collection of Baillieu Library, the University of Melbourne, is custodian to a very fine 19th century manuscript of Haft-Band (Seven Strophes) by the 14th century devotional poet Mullā Ḥassan Kāshī. This illuminated manuscript is most probably of Indian origin. It is penned in superb Nasta’liq script by Muḥammad Amir Raẓavi/Riẓvi in the age of 95. The volume begins with an attractive sarlowḥ, and concludes with a beautiful colophon and an additional interesting page at the end of the manuscript. Subjects discussed in this paper are arranged under nine headings. After a brief ‘Introduction,’ a short passage is allocated to the significance of number seven under ‘Symbolism of Seven and the Haft-Band Genre.’ A concise biography of the poet, his beautiful mausoleum, and the importance of his Haft-Band are discussed under ‘Ḥassan Kāshī’. ‘A Mystical Dream’ provides an insight into a chain of historical events that were inspired and initiated by the poet’s stunning dream, which eventually led to the wide acceptance of the Haft-Band. Before Kāshī, the genre of madḥ (praise) was almost exclusively dedicated to kings and rulers for a reward. Kāshī transformed the trend of praise poetry by shifting the focus of the praise. This matter is discussed under ‘From Praising Kings to Religious Devotion.’ A glimpse of Kāshī’s genius mind and poetic mastery is presented under ‘Seven Openings & Seven Closings’. The next heading, ‘About the Manuscript’ provides an analytical study of the manuscript, from codicological perspectives. ‘Scribe and Colophon’ and ‘A Stunning Ending’ are titles of passages dedicated to introducing the old scribe’s world and his personal poetic taste.